Odpowiedź :
Odpowiedź:
A)
[tex]6 \sqrt{7 } + 2(3 - 27) = \\ 6 \sqrt{7} + 2 \times ( - 24) =\\ 6 \sqrt{7 - 48} [/tex]
B)
[tex]3 - 25 - ( \frac{4}{5} - 6) = \\ - 22 - ( - \frac{26}{5} ) = \\ - 22 + \frac{26}{5} = \\ - \frac{84}{5 } = \\ - 16 \frac{4}{5} [/tex]
C)
[tex] - 376 - 3 \times ( \frac{1}{2} \div 6) = \\ - 376 - 3 \times ( \frac{1}{2} \times \frac{1}{6} ) = \\ - 376 - 3 \times \frac{1}{12} = \\ - 376 \frac{1}{4} [/tex]
D)
[tex]5(2 + \frac{4}{3} ) + 2(3 - 5) = \\ 5 \times \frac{10}{3} + 2 \times ( - 2) = \\ \frac{50}{3} - 4 = \\ \frac{38}{3} = \\ 12 \frac{2}{3} [/tex]
E)
[tex]3(2 - \sqrt{2} ) - (572 + 4) = \\ 6 - 3 \sqrt{2} - 576 = \\ - 570 - 3 \sqrt{2} [/tex]
F)
[tex] - 205 - 17( - 30247 + 3) = \\ 205 - 17( - 30244) = \\ - 205 + 514148 = \\ 513943[/tex]